2014
DOI: 10.1038/ki.2013.508
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in 12 known dominant disease-causing genes clarify many congenital anomalies of the kidney and urinary tract

Abstract: Congenital anomalies of the kidney and urinary tract (CAKUT) account for approximately half of children with chronic kidney disease. CAKUT can be caused by monogenic mutations, however, data are lacking on their frequency. Genetic diagnosis has been hampered by genetic heterogeneity and lack of genotype-phenotype correlation. To determine the percentage of cases with CAKUT that can be explained by mutations in known CAKUT genes, we analyzed the coding exons of the 17 known dominant CAKUT-causing genes in a coh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
190
2
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 214 publications
(208 citation statements)
references
References 46 publications
(41 reference statements)
12
190
2
4
Order By: Relevance
“…4 Recently, it was shown that a monogenic cause can be detected in approximately 12% of patients. 2,[5][6][7][8] The documented mode of inheritance in most published pedigrees is compatible with an autosomal dominant inheritance with variable expressivity and incomplete penetrance. 2 However, several CAKUT-causing genes with autosomal recessive mode of inheritance have been recently identified.…”
mentioning
confidence: 76%
See 1 more Smart Citation
“…4 Recently, it was shown that a monogenic cause can be detected in approximately 12% of patients. 2,[5][6][7][8] The documented mode of inheritance in most published pedigrees is compatible with an autosomal dominant inheritance with variable expressivity and incomplete penetrance. 2 However, several CAKUT-causing genes with autosomal recessive mode of inheritance have been recently identified.…”
mentioning
confidence: 76%
“…Mutations in all genes known to be mutated in isolated CAKUT in humans were excluded previously in this cohort. 6 In addition, a clinical diagnosis of a known monogenic syndrome had not been previously made in any of the patients.…”
mentioning
confidence: 99%
“…They also studied 124 families with VUR or VUR-other CAKUT and identified two heterozygous missense variants of the gene in two unrelated families (British and Dutch) with VUR-renal hypoplasia, VUR, VUR-duplex kidney, and other CAKUT-small kidney. A study families, in which the most common phenotypes were VUR, renal hypodysplasia, and unilateral renal agenesis; four mutations of ROBO2 were detected in four unrelated families (14). Three linkage studies, however, have been unable to support these findings.…”
Section: Discussionmentioning
confidence: 89%
“…Recent studies have identified variants of the roundabout, axon guidance receptor, homolog 2 (ROBO2) gene in patients with VUR and VUR accompanied by other CAKUT, but their conclusions are contradictory on whether or not mutations of the ROBO2 gene are a causative factor of VUR or VUR-other CAKUT (6)(7)(8)(9)(10)(11)(12)(13)(14).…”
mentioning
confidence: 99%
“…Las anomalías congénitas de los riñones y de las vías urinarias (CAKUT por sus siglas en Inglés Congenital Anomalies of the Kidney and Urinary Tract), se presentan entre 3 a 6 casos por cada 1000 nacidos vivos 1 , se ha reportado, que están presentes hasta en el 55% de la insuficiencia renal en el niño y adolescente. Su detección prenatal mediante ultrasonografía realizada por medicina materno fetal es variable por diversas condiciones, oscilando entre menos del 30% a más del 80% en algunas regiones 2 .…”
Section: Introductionunclassified